Rekonsiliasi Data Keuangan Pemerintah Pasca Penerapan Single Database Sakti Menggunakan Finite State Automata - Khuluq, Anjahul; Gata, Windu; Putra, Jordy Lasmana; Novitasari, Hafifah Bella (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Reconciliation of government financial data is a process of pairing data between work unit data and State General Treasurer data to be able to produce accountable and credible central government financial reports. The current reconciliation process is carried out by uploading data by the work unit to the e-rekon application, which can be replaced by an automatic process when implementing the single SAKTI database. The use of Finite State Automata in providing validation when the reconciliation process is carried out has proven to be able to help make the Government Financial Data Reconciliation Process effective and efficient